2016
DOI: 10.1007/s10561-016-9564-7
|View full text |Cite
|
Sign up to set email alerts
|

Deceased tissue donor serology and molecular testing for HIV, hepatitis B and hepatitis C viruses: a lack of cadaveric validated tests

Abstract: Vital to patient safety is the accurate assessment and minimization of risk for human immunodeficiency virus (HIV), Hepatitis C (HCV), and Hepatitis B (HBV) virus transmission by deceased donor organ and tissue transplantation. The pathogens are tested by serological kits based on enzyme-linked immunosorbent assay (ELISA), chemiluminescence (CLIA) and eletrochemiluminescence (ECLIA) immunoassays. Organ transplantation is a highly successful life-saving treatment in Brazil, but the Brazilian Health Surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…However, unclaimed bodies used for research and teaching purpose may only be received at universities weeks after death. Furthermore, the viral load is affected by hemodilution, duration of the disease, and adherence of antiretroviral treatment (Cavanaugh and King ; LeFor et al ; Gala et al ; Heim et al ; Greenwald et al ; Kurian et al ; Wilkemeyer et al ; Victer et al ; Prince and Hale ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, unclaimed bodies used for research and teaching purpose may only be received at universities weeks after death. Furthermore, the viral load is affected by hemodilution, duration of the disease, and adherence of antiretroviral treatment (Cavanaugh and King ; LeFor et al ; Gala et al ; Heim et al ; Greenwald et al ; Kurian et al ; Wilkemeyer et al ; Victer et al ; Prince and Hale ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, hemolysis influences HIV protein detection by Western blot and can produce false positive results (Guan ). With NAT, hemolysis may inhibit amplification of viral nucleic acids (Strong et al ; Meyer et al ; Victer et al ). No mention has been made on the effect of hemolysis on rapid HIV assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported detection of salivary CA15-3 with ELISA but not with ECLIA and CLIA (13). We chose to evaluate detection of CA15-3 using CLIA and ECLIA because these techniques are used routinely in clinical exams for evaluation of serum tumor markers and serology of viral infectious agents (17). Recently, CLIA was used to evaluate proteins in liquor, demonstrating that the method can be used to analyze different fluids, such as saliva (17).…”
Section: Discussionmentioning
confidence: 99%